2016
DOI: 10.1177/1933719115620495
|View full text |Cite
|
Sign up to set email alerts
|

rhTNFR: Fc Suppresses the Development of Endometriosis in a Mouse Model by Downregulating Cell Proliferation and Invasiveness

Abstract: Tumor necrosis factor α (TNF-α), a proinflammatory cytokine, may play an important role in the pathogenesis of endometriosis; therefore, TNF-α inhibitors potentially have an effect on endometriosis. To investigate the effect of anti-TNF-α treatment on endometriosis, 2 TNF-α inhibitors: recombinant human TNF receptor: Fc fusion protein (rhTNFR: Fc) and TNF-α monoclonal antibody (TNF-α mAb) were used to treat human eutopic endometrial stromal cells (hESCs), and the effects on cell survival, cell cycle, and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
(59 reference statements)
0
3
0
1
Order By: Relevance
“…It is important to emphasize that the TNFRp55−/− mice lack expression of TNFRp55 but display normal numbers of high affinity TNFRp75 molecules (Pfeffer et al 1993). In surgically induced endometriosis in rat and mouse, the treatment with etanercept, a fusion protein consisting of human recombinant soluble TNFRp75 conjugated to a human Fc antibody subunit, was associated with negative immunohistochemical staining for TNFRp75 and reduced endometriosis development (Islimye et al 2011, Liu et al 2016. These data indicate that the lack of activity of the TNFRp75, a receptor associated mainly with proliferation, cell survival and angiogenesis (Haider et al 2009, Cabal-Hierro & Lazo 2012, suppresses the development of endometriosis and that the effects observed in TNFRp55 deficient animals of the present study may be due to activation of TNFRp75-dependent pathways.…”
Section: :3mentioning
confidence: 99%
“…It is important to emphasize that the TNFRp55−/− mice lack expression of TNFRp55 but display normal numbers of high affinity TNFRp75 molecules (Pfeffer et al 1993). In surgically induced endometriosis in rat and mouse, the treatment with etanercept, a fusion protein consisting of human recombinant soluble TNFRp75 conjugated to a human Fc antibody subunit, was associated with negative immunohistochemical staining for TNFRp75 and reduced endometriosis development (Islimye et al 2011, Liu et al 2016. These data indicate that the lack of activity of the TNFRp75, a receptor associated mainly with proliferation, cell survival and angiogenesis (Haider et al 2009, Cabal-Hierro & Lazo 2012, suppresses the development of endometriosis and that the effects observed in TNFRp55 deficient animals of the present study may be due to activation of TNFRp75-dependent pathways.…”
Section: :3mentioning
confidence: 99%
“…The decreased apoptosis and the improved cell survival are often reported in eutopic and ectopic endometrium of affected woman as compared to healthy controls, and some studies investigated the effect of different plants on apoptosis and cell survival [57][58][59][60]. Similarly, other pathways having a key role in the development of endometriosis were investigated as possible target of phytotherapy [56], such as angiogenesis mediated by vascular endothelial growth factor (VEGF) [49,61], the altered inflammatory microenvironment involving cytokines and immune cells [62][63][64], the oxidative stress [65,66], and the attachment and invasion mechanisms [67][68][69]. Moreover, there is evidence that specific herbs may have an impact on the epigenome, representing a therapeutic strategy to potentially reverse the aberrant epigenetic changes reported in endometriosis [70,71].…”
Section: Phytotherapymentioning
confidence: 99%
“…In baboons, anti-TNF-α inhibits the development of lesions significantly, but fails to increase pregnancy rates, fecundity levels per cycle, time to pregnancy, and cumulative pregnancy rates ( 54 , 55 ). In vitro studies have shown that regression of lesion size, as well as decreased expression of inflammatory cytokines after anti-TNF-α administration ( 56 , 57 , 58 , 59 , 60 , 61 ). Mild side-effects may include headache and allergic reactions during intravenous administration, whereas long-term administration is associated with serious infections and tuberculosis reactivation ( 51 , 62 ).…”
Section: Novel Medical Therapiesmentioning
confidence: 99%